Domestic cat growth through a logistic model - Parés-Casanova, Pere M. (2018)
The objective of the study was to describe and analyze the growth pattern of the domestic cat. A total of 68 cats (37 males and 31 females, with an age range of 1.4-84 and 1.5-84 months, respectively), of undefined racial composition, from the urban area of the municipality of Arauca, Colombia were studied. Age, body length, pelvic girth, skull perimeter, and fore and hind right limb lengths were recorded. Growth was determined for each sex with the logistic equation y=a/(1+be-cx). Results showed a similar growth pattern between sexes, except for hind limb length (p=0.033), which presented an initial accelerated growth with an ulterior asymptotic growth in females, but there were few changes in males. Final size was similar for both sexes. This study constitutes a first contribution to growth models in domestic cats.